MENINGKATKAN KECERDASAN EMOSI SISWA REMAJA MELALUIPENDIDIKAN JASMANI DAN OLAHRAGA DI SEKOLAH - - Komarudin (Jurnal Pendidikan Jasmani Indonesia, 2014)
AbstractTeenage students is the next generation that carries on the future of the nation and the state, to develop the potentialof the students to become a man of faith and piety to God Almighty, noble, healthy, knowledgeable, capable, creative,independent, and become citizens of a democratic and responsible. In fact, all teenage students can succeed andformed in accordance with the educational objectives. This failure occurred since there was no possible formation ofemotional maturity in young students, in this case a very large role, even sometimes more influential than someone’smind, especially during the youth period. Physical Education was given at school because it had a purpose thatwas comprehensive which included aspects of physical, cognitive, affective, emotional, social, and moral. PhysicalEducation was a process of interaction between the students and the environment managed through physical activitysystematically to form the whole person, which was to develop physical, psychomotor, cognitive, and affectiveaspects. A personhad the emotional maturity if he or she could fulfill these aspects including: being realistic, acceptedthemselves and others as they were, adaptable, able to resolve the issue in an objective perception, not dependenton others, concerned with the values of ethics and morality, able to empathize, had a sense of humor, creativity andfond of a challenge. All aspects of emotional maturity could be formed through Physical Education, for example:being sportive enough to recognize the win of the opponent, easy to adjust, believe in self and so on.Keywords: Emotional intelligence, Teenage students, Physical EducationAbstrakSiswa remaja merupakan generasi penerus untuk melanjutkan pembangunan bangsa dan negara, untukmengembangkan potensi peserta didik agar menjadi manusia yang beriman dan taqwa kepada Tuhan Yang Maha Esa,berakhlak mulia, sehat, berilmu, cakap, kreatif, mandiri, dan menjadi warga negara yang demokratis serta bertanggungjawab.Pada kenyataannya tidak semua siswa remaja dapat berhasil dan terbentuk sesuai dengan tujuan pendidikantersebut di atas.Kegagalan terjadi dimungkinkan tidak terbentuknya kematangan emosi pada siswa remaja, pada halini memegang peranan sangat besar, bahkan terkadang lebih berpengaruh daripada pikiran seseorang terutama padamasa remaja.Penjasor diberikan di sekolah karena penjasor memiliki tujuan yang bersifat menyeluruh yang mencakupaspek fisik, kognitif, afektif, emosional, sosial dan moral. Pendidikan Jasmani merupakan suatu proses interaksiantara siswa dan lingkungan yang dikelola melalui aktivitas jasmani secara sistematik untuk membentuk manusiaseutuhnya, yaitu untuk mengembangkan aspek physical, psychomotor, cognitif, dan aspek affektif.Seseorang yangmemiliki kematangan emosinya jika dapat memenuhi aspek-aspek antara lain meliputi : bersikap relistik, menerimadiri sendiri dan orang lain seperti apa adanya, mudah menyesuaikan diri, mampu menyelesaikan persoalan secaraobyektif, tidak tergantung pada orang lain, mementingkan nilai-nilai etik dan moral, mampu berempati,, mempunyairasa humor, memiliki kreativitas serta senang tantangan. Semua aspek-aspek kematangan emosi tersebut dapatdibentuk melalui penjasor, sebagai contoh : sportif mengakui kehebatan lawan, mudah menyesuaikan diri, percayapada diri pribadi dan sebagainya.Kata kunci :Kecerdasan emosi, Siswa remaja, Penjasor